2016
DOI: 10.1160/th15-12-0985
|View full text |Cite
|
Sign up to set email alerts
|

Increased von Willebrand factor, P-selectin and fibrin content in occlusive thrombus resistant to lytic therapy

Abstract: Therapeutic fibrinolysis is ineffective in 40 % of ST-segment elevation acute myocardial infarction (STEMI) patients, but understanding of the mechanisms is incomplete. It was our aim to compare the composition of coronary thrombus in lysis-resistant STEMI patients with that of lysis-sensitive patients. Intracoronary thrombi (n=64) were obtained by aspiration in consecutive STEMI patients. Of them, 20 had received fibrinolysis and underwent rescue percutaneous coronary intervention (r-PCI, lysis-resistant pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 38 publications
1
10
0
1
Order By: Relevance
“…Prior studies on fibrin formation and clot resistance have demonstrated that slow growing clots with multiple side branches are fibrinolytic resistant. 29,30 This was supported by our data in which TEG angle (a measurement of fibrinogen function) was inversely related to OSp in the AR chip in the presence of t-PA, whereas LY30 unexpectedly inversely correlated with OT. As the PL chip neglects any contribution of fibrinogen to clot, these patients potentially could have had an adaptive response to downregulate their platelets from increased fibrinogen function.…”
Section: Discussionsupporting
confidence: 62%
“…Prior studies on fibrin formation and clot resistance have demonstrated that slow growing clots with multiple side branches are fibrinolytic resistant. 29,30 This was supported by our data in which TEG angle (a measurement of fibrinogen function) was inversely related to OSp in the AR chip in the presence of t-PA, whereas LY30 unexpectedly inversely correlated with OT. As the PL chip neglects any contribution of fibrinogen to clot, these patients potentially could have had an adaptive response to downregulate their platelets from increased fibrinogen function.…”
Section: Discussionsupporting
confidence: 62%
“…The major drawback of this study were the inadequate financial resources, which limited the sample size. However, the number of the included patients was not much smaller than in other PAI-1 studies in acute coronary syndromes ( 7 , 17 , 29 , 30 ). Post-hoc power analysis showed that χ 2 and Mann-Whitney U tests for determining the difference in PAI-1 activities between dead and alive patients at 5-year follow-up had adequate power (1.000 for both tests at 5% significance level, G*Power 3.1.9.3, Heinrich-Heine-Universität Düsseldorf, Düsseldorf, Germany) ( 31 ).…”
Section: Discussionmentioning
confidence: 85%
“…Higher plasma PAI-1 concentrations were detected in acute STEMI patients with fibrinolysis-resistant thrombi ( 17 ), while higher PAI-1 rise was detected in patients treated with streptokinase and persistent coronary artery occlusion ( 18 ). This indicates that PAI-1 rise influences the outcome similarly regardless of the reperfusion strategy.…”
Section: Discussionmentioning
confidence: 99%
“…When the platelets are stimulated, it is rapidly expressed on the surface of the platelet membrane, which mediates the adhesion of platelets and vascular endothelium to the inflammatory cells and the adhesion of platelets, and promotes fibrin deposition and thrombosis to form ( Qi and Wang, 2014 ). CD62p is currently one of the most specific indicators that can reflect platelet activation ( Bonacina et al, 2016 ; Sambola et al, 2016 ). The results showed that, compared with CG, the expression of CD62p in the MG increased significantly, indicating that the platelet activation was enhanced, which was consistent with the blood stasis syndrome.…”
Section: Discussionmentioning
confidence: 99%